Chitosan-immobilized lipases for the catalysis of fatty acid esterifications - Foresti, María Laura; Ferreira, María Luján (Enzyme and Microbial Technology)
Lipases from Candida rugosa, Pseudomonas fluorescens and Candida antarctica B were immobilized onto chitosan and glutaraldehyde-pretreated chitosan powders. The prepared biocatalysts were assayed in the direct esterification of oleic acid and ethanol to produce the ethyl oleate. In order to maximize ester production and avoid solvent-related costs (the solvent itself, solvent recovery and solvent recycle), the synthesis of ethyl oleate was performed in a solvent-free system. The different structures of the lipases chosen for the catalysis led to very different activity levels, with C. antarctica B derivatives being the most active ones. The parametric study performed revealed that the best operation conditions for ester synthesis are found at mild temperatures (35-45 °C), and in "biphasic systems" (two liquid phases), generated upon addition of relatively high quantities of water to the mixture of substrates. The reduction of the concentration of water in the organic reactive phase of biphasic systems favored ester synthesis, with higher ester yields in the first hours of reaction than those measured in systems with no added water. In the optimum conditions mentioned the biocatalyst resulting from the immobilization of lipase from C. antarctica B onto untreated chitosan powder led to 75% conversion of the fatty acid in 24 h of reaction. The stability of this catalyst also proved to be very attractive with five consecutive 24 h uses with a residual activity of 90-95%. Fil: Foresti, María Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Ferreira, María Luján. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina